Kimihia hauora Māori = Māori health policy and practice : a thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy, Massey University, Albany, New Zealand - Kiro, Cynthia A., Ngāpuhi, Ngāti-Hine, Ngāti Te Rangiwewehe (Massey University, 2001)
Health reforms in New Zealand during the 1990s introduced a new term to our lexicon, 'by Māori for Māori providers'. These providers are an expression of a policy attempt to marry two distinctive government intentions in respect of Māori. One intention was the inclusion of Māori to address political concerns such as tino rangatiratanga (Māori control over Māori lives). The other was the devolution of responsibility for Māori health outcomes to the Māori community itself, in line with other neo-liberal policies adopted between 1984 and 1999. This research examines the effects of the health reforms announced in 1991 in respect of Māori health policy and Māori health services within the Auckland region. In particular, the research is concerned with how North Health enacted these reforms. North Health was the northernmost Regional Health Authority responsible for the largest Māori population in New Zealand, the largest metropolitan centre, and areas of high Māori health need in Northland, South Auckland and West Auckland. They developed a distinctive approach to Māori health policy that would have pervasive and lasting effects on health policy in the rest of the country. In particular, their identification of three strategies for Māori health purchasing, including support for by Māori for Māori providers, mainstream enhancement and Māori provider development, formed the basis of Māori health services within Auckland for many years. This thesis is not an attempt to tell the story of the Māori health providers who form the basis of the case studies. Many have started this process themselves. Rather, it is an attempt to place their experiences within the broader context of public policy analysis during a period of considerable change in New Zealand. It also provides an opportunity for understanding the ideas of North Health as the health services purchaser. These ideas remain as significant influences on current Māori health policy through the Health Funding Authority. Furthermore, this more contextualised analysis is consistent with the Ottawa Charter's emphasis on healthy public policy. Such policy must take account of its impact on the well-being of populations within society. This policy is not limited solely to that of the health sector, but includes all public policy that impacts on health such as housing, education, income maintenance and other significant social factors. While a great deal has been written about the health reforms in New Zealand, little has been written about the implications of these reforms for Māori. Even less has been written about the specific experiences of Māori providers and the policies the underpin Māori health services and health in New Zealand. The research found that there has been considerable innovation on the part of Māori policy makers and purchasers in an attempt to shift resources to Māori communities to provide services themselves. This was part of a broader move within government policy to devolve responsibility for service provision and risk to communities of interest from the late 1980s to 1999. Strategies to promote by Māori for Māori providers enabled Māori communities (especially iwi communities) to become more directly involved in health decisions and service provision, but they also allowed weakened government accountability for Māori health outcomes. While Māori providers have displayed considerable innovation and energy in establishing services. They have developed a distinctive community development approach that is at the forefront of changes in primary care incorporating community health workers, extensive community networks and health promotion programmes. However, these elements are often under-valued within their services and they remain heavily dependent upon the GP service at the core of their health centres. Mainstream enhancement among large health providers has been largely an afterthought considered too difficult and without the political rewards of independent Māori providers. Yet the overwhelming majority of Māori continue to use mainstream services and therefore require urgent reorientation of these services to better meet their needs. The provision of local Māori services is an essential complement to what already exists and these should be strengthened and promoted because they provide suitable primary care models of care for all New Zealanders. However, this approach must be part of a broader population based and macro policy approach that informs government policies that impact on Māori health and wellbeing. The provision of highly targeted primary care services will not change Māori health status without the accompanying shift in macro-environments such as labour market participation, cultural pride and greater egalitarianism.
Keywords: Maori (New Zealand people); Health and hygiene; Medical policy; New Zealand; Hauora; Kaupapa whakaaro; Tāngata whenua; Tuku ratonga; Māori Doctoral Thesis; 451006 Ngā kaupapahere hauora o te Māori (Māori health policy)